(untitled) (Research, Society and Development, 2020)
The recognition of the importance of evolution for biology is well known and pointed out by several researchers and historians of science. Given this fact, our objective with this investigation was to identify in the conceptions of thirteen biology teachers, in the initial formation, an importance attributed by them and their conceptions of biological evolution. Therefore, we collected the data through a questionnaire and video recordings of biweekly meetings with the research subjects, academics from a state university in the State of Paraná. These data were categorized and built a metatext from the Textual Discursive Analysis (ATD). We identified that teachers in initial training are aware of the epistemological importance of evolution for scientific biology, however they presented concepts of evolution based on synthetic theory, which demonstrates a lack of interaction of the most current debates about evolutionary mechanisms and processes.